BISPHOSPHONATE-RELATED OSTEONECROSIS OF THE JAW AND DENTAL IMPLANTS - Ala Hassan A. Qamheya; Sinem Yeniyol; Volkan Arısan (Journal of Istanbul University Faculty of Dentistry, 2016)
Bisphosphonate (BP) is one of the possible riskfactors in the osteonecrosis of the jaw (ON J). Surgical interventions during or after the course of treatment by using BPs may expose the patient under this risk. Animal studies, human studies, case reports, and systematic reviews are used to show the relationship between the use of bisphosphonates and dental implants. In this review data about bisphosphonaterelated osteonecrosis of the jaw (BRON J): incidence, prevention and treatment modalities for the patients who are scheduled for dental implant treatment plan and who have been already treated by dental implants will be investigated. Various views for the relationship between dental implants and bisphosphonates will be analyzed depending on the multifactors: duration, route of uptake, dosage of the drug and patient’s other medications that affect the effects of bisphosphonate. All patients treated with this drug must be informed about the risk of implant loss or possibility of osteonecrosis.